PENGEMBANGAN BUKU KERJA BERBASIS REALISTIK UNTUK MATERI SEGIEMPAT DAN SEGITIGA PADA PEMBELAJARAN MATEMATIKA KELAS VII SMPN 17 PADANG - Arvita, Widia - (Pendidikan Matematika, 2014)
The background of the research was about the importance of teaching material in learning process.The expected teaching material was the teaching material that proposes the real problem in thebeginning of learning involving the students to build a concept so that the students were able to studyindependently. Therefore, it was made a teaching material in the form of a realistic-based work bookfor the triangle and rectangle material on the seventh grade of Public Junior High School 17 Padang.The research was to know the validity and practice of the realistic-based work book. The type of theresearch was the development by using 4-D model. 4-D model consists of 4 stages of development,i.e. 1) define, 2) design, 3) develop, and 4) disseminate. The research was only conducted into threestages, i.e. define stage, design stage, and develop stage. The validity test result of realistic-based workbook of very valid criteria was 85,88%. The student practical test result of very practical category was95.66%. Meanwhile, the teacher practical test result was 85.00%. It can be concluded that the realisticbasedwork book was valid and practical.